HAMBATAN PELAKSANAAN KIE HIV/AIDS DALAM PELAYANAN ANC OLEH BIDAN DI PUSKESMAS DI KOTA YOGYAKARTA - Hastuti, Sari; Theresia, Endah Marianingsih; Lianawati, Sri Hendy (Jurnal Kesehatan Ibu dan Anak, 2012)
Indonesia has entered into a concentrated epidemic level since 2000, namely the high-risk groups, HIV/AIDS prevalence exceeds 5%. City of Yogyakarta is one area that comes into the accelerated program of 105 districts/cities in Indonesia and has been providing HIV testing services at the clinic. AIDS prevention commission province of Yogyakarta reported since the year 2009 in 2003-2008 was 23 positive children with HIV, in 2005-2008 recorded a pregnant woman gave birth to HIV-positive and 10 peoples. PMTCT package integrated with maternal and child health and family planning services so that midwives in each clinic to get the socialization of PMTCT. Objectives: to determine the inhibiting factors of Communication, information and Education on HIV /AIDS in the antenatal care services by midwife in supporting PMTCT programs in health centers city of Yogyakarta. This type of research is qualitative research field. The research location was taken in 13 health centers in the city of Yogyakarta, the main respondent are midwives in the outpatient maternal and child health services, each clinic taken a midwife who has got the socialization and training of PMTCT programs with in-depth interviews. Additional respondents are policy makers and clients. Analysis of data using content analysis of data while checking the validity of the method triangulation methods and sources. Results: the results of in-depth interviews found eight categories of theme as inhibiting factors.